Part A
x = some unknown number
x+8 = add on 8 to the number
3(x+8) = triple the previous result
Therefore, one equation to set up is 3(x+8) = 66
This is the same as 3x+24 = 66 because 3(x+8) = 3x+3*8 = 3x+24. Use the distributive property to multiply that outer 3 to each term inside.
Answers:
C) 3x+24 = 66
D) 3(x+8) = 66
============================================================
Part B
Let's solve for x. I'll show the steps for each equation mentioned. When you write out the steps, you probably only need to pick one equation to solve.
3(x+8) = 66
x+8 = 66/3
x+8 = 22
x = 22-8
x = 14
Or
3x+24 = 66
3x = 66-24
3x = 42
x = 42/3
x = 14
Either way, we get the same x value. To confirm this answer, replace x with 14 in either equation and simplify fully. You should get 66 on both sides.
Answer: x = 14